High-dimensional mass cytometry identifies T cell and B cell signatures predicting reduced risk of Plasmodium vivax malaria - Lisa J. Ioannidis (2022)
IFN-γ–driven responses to malaria have been shown to modulate the development and function of T follicular helper (TFH) cells and memory B cells (MBCs), with conflicting evidence of their involvement in the induction of antibody responses required to achieve clinical immunity and their association with disease outcomes. Using high-dimensional single-cell mass cytometry, we identified distinct populations of TH1-polarized CD4+ T cells and MBCs expressing the TH1-defining transcription factor T-bet, associated with either increased or reduced risk of Plasmodium vivax (P. vivax) malaria, demonstrating that inflammatory responses to malaria are not universally detrimental for infection. Furthermore, we found that, whereas class-switched but not IgM+ MBCs were associated with a reduced risk of symptomatic malaria, populations of TH1 cells with a stem central memory phenotype, TH17 cells, and T regulatory cells were associated with protection from asymptomatic infection, suggesting that activation of cell-mediated immunity might also be required to control persistent P. vivax infection with low parasite burden.